PENGARUH STRATEGI DIVERSIFIKASI TERHADAP KINERJA KEUANGAN PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING(PADA PERUSAHAAN SEKTOR PROPERTI DAN REAL ESTATE DI BURSA EFEK INDONESIA PERIODE 2009-2013) - SULASTRI, ULI (Jurnal Akuntansi AKUNESA, 2015)
Abstract:The purpose of this study was to determine how the diversification strategy influence the performance of the company with the capital structure. This research was conducted on the company property and real estate sectors listed of Indonesia Stock Exchange in 2009-2013. The method of Sample selection used purposive sampling and obtained 90 samples of data. The analysis technique used linear regression with intervening variables.The results showed that the diversification strategy does not affect the corporate's financial performance and capital structure, while the capital structure give the positive effect on the financial performance. In conclution, the indirect effect of diversification strategy didn’t give the influence on financial performance through the capital structure. In short, the capital structure not a mediator for diversification strategy in to the corporate’s financial performance.Keywords: Diversification strategy, Capital Structure, Corporate’s Financial Performance